Moral and exhausting distress working in the frontline of COVID-19: a Swedish survey during the first wave in four healthcare settings - Mia Svantesson; Lars Sandman; Linda Durnell; Erik Hammarström; Gustav Jarl (BMJ Open)
Objectives To describe the prevalence and sources of experienced moral stress and anxiety by Swedish frontline healthcare staff in the early phase of COVID-19.Design Cross-sectional survey, quantitative and qualitative.Participants and setting 1074 healthcare professionals (75% nurses) in intensive, ward-based, primary and municipal care in one Swedish county.Measures A study-specific closed-ended and an open-ended questionnaire about moral stress and the Generalised Anxiety Disorder 7-item scale measuring anxiety, followed by an open question about anxiety.Findings Moral stress was experienced by 52% of respondents and anxiety by 40%. Moral stress in concern for others attributed to institutional constraints comprised experiences of being deprived of possibilities to respond to humane and professional responsibility. Staff experienced being restricted in fulfilling patients’ and families’ need for closeness and security as well as being compelled to provide substandard and inhumane care. Uncertainty about right and good, without blame, was also described. However, a burdensome guilt also emerged as a moral distress, blaming oneself. This comprised feeling complicit in the spread of COVID-19, inadequacy in care and carrying patients’ suffering. Staff also experienced an exhausting distress as a self-concern in an uncontrollable work situation. This comprised a taxing insecurity by being in limbo, being alone and fear of failing, despair of being deprived control by not being heard; unable to influence; distrusting management; as well as an excessive workload.Conclusions We have not only contributed with knowledge about experiences of being in the frontline of COVID-19, but also with an understanding of a demarcation between moral stress/distress as a concern for patients and family, and exhausting distress in work situation as self-concern. A lesson for management is that ethics support should first include acknowledgement of self-concern and mitigation of guilt before any structured ethical reflection. Preventive measures for major events should focus on connectedness between all parties concerned, preventing inhumane care and burn-out.